Phylogenomics of Lasiodoriforms: reclassification of the South American genus Vitalius Lucas, Silva and Bertani and allied genera (Araneae: Theraphosidae) - Galleti-Lima, Arthur; Hamilton, Chris A.; Borges, Leandro M.; Guadanucci, José Paulo L. (Frontiers in Ecology and Evolution, 2023)
Theraphosinae is the most diverse subfamily of Theraphosidae spiders, but their evolutionary history still remains unanswered. This problem is common in taxonomic groups with phylogenetic hypotheses that have, often been based only on qualitative morphological characters and, rarely, molecular analyses. Phylogenomics has significantly contributed to the understanding of the evolution of many non-model groups, such as spiders. Herein, we employ Ultraconserved Elements (UCEs) phylogenomics to propose a new hypothesis for a group of Theraphosinae genera, namely Lasiodoriforms: Vitalius, Lasiodora, Eupalaestrus, Pterinopelma, Proshapalopus and Nhandu. We propose three genera (Parvicarina, Lasiocyano and Tekoapora) and their respective morphological diagnoses are provided. Our phylogeny supports the transfer of species from the genus Vitalius to Pterinopelma (P. logisternalis and P. roseus) and Proshapalopus (P. nondescriptus) and from Proshapalopus to Eupalaestrus (E. anomalus). Finally, we describe a new species of Vitalius (Vitalius australis sp. nov.) from Southern Brazil. Based on these three new generic descriptions and transferred species, the Lasiodoriform tarantulas comprise nine genera from Argentina, Brazil, Paraguay, and Uruguay, and the genus Vitalius now includes seven species.